2022
DOI: 10.1039/d2ta01544g
|View full text |Cite
|
Sign up to set email alerts
|

Crystal facet effects of platinum single-atom catalysts in hydrolytic dehydrogenation of ammonia borane

Abstract: The Pt1/Co3O4-c catalysts exhibit great catalytic activities in hydrolytic dehydrogenation of ammonia borane (AB) with a specific rate of 6035 molH2 molPt-1 min-1 at room temperature. In-situ DRIFTS spectra and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…The facet effect has also been demonstrated in other oxide-supported ADMCs. For example, Pt single atoms supported on Co 3 O 4 cubes, Co 3 O 4 truncated octahedra, and Co 3 O 4 octahedra (Figure a–d) exhibited completely different hydrogen production activities in the hydrolytic dehydrogenation of ammonia borane . Experiments and theoretical calculations showed that the electron transfer from single Pt sites to supports was influenced by the different exposed surfaces of supports.…”
Section: Atomically Dispersed Metal Catalysts As Model Catalystsmentioning
confidence: 75%
See 2 more Smart Citations
“…The facet effect has also been demonstrated in other oxide-supported ADMCs. For example, Pt single atoms supported on Co 3 O 4 cubes, Co 3 O 4 truncated octahedra, and Co 3 O 4 octahedra (Figure a–d) exhibited completely different hydrogen production activities in the hydrolytic dehydrogenation of ammonia borane . Experiments and theoretical calculations showed that the electron transfer from single Pt sites to supports was influenced by the different exposed surfaces of supports.…”
Section: Atomically Dispersed Metal Catalysts As Model Catalystsmentioning
confidence: 75%
“…The more electron depletion and higher oxidation state of the Pt center were found in Pt 1 /Co 3 O 4 -c, which was beneficial to the adsorption of ammonia borane and the dissociation of H 2 . Thus, a better catalytic activity was observed over the Pt 1 /Co 3 O 4 -c catalyst on Co 3 O 4 (100) than Pt 1 /Co 3 O 4 -t and Pt 1 /Co 3 O 4 -o with other exposed facets (Figure e) . Isolated Pt or Au atoms were successfully deposited onto TiO 2 with different exposed facets, i.e.…”
Section: Atomically Dispersed Metal Catalysts As Model Catalystsmentioning
confidence: 96%
See 1 more Smart Citation
“…AB was applied in fuel cells in two ways: one is as a hydrogen storage material to produce H 2 [16][17][18][19][20] and another is as an anode fuel directly. 21,22 As the indirect application of AB, the dehydrogenation of AB has been widely studied in recent years owing to its high gravimetric hydrogen density (19.6 wt% H), and there are three methods to promote the dehydrogenation of AB, including thermolysis, [23][24][25][26] hydrolysis, 16,[27][28][29] and alcoholysis.…”
Section: Introductionmentioning
confidence: 99%
“…The binding energy at 72.7 eV was higher than that for Pt 4f 7/2 of Pt 2+ species (72.1 eV), but lower than that for Pt 4f 7/2 of Pt 4+ species (74.2 eV), so it could be attributed to Pt 4f 7/2 of Pt δ+ species (2 < δ < 4). [32][33][34][35] The X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) measurements were performed to obtain detailed information about the chemical environment of Pt 1 /Fe 2 O 3 . The XANES results showed that the white line peak intensity of Pt 1 /Fe 2 O 3 was lower than that of PtO 2 but higher than that of Pt foil (Fig.…”
mentioning
confidence: 99%